Macedonians in the Greek-Italian War (1940–1941) - Panovska, Liljana (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the situation of the Macedonian population living in northern Greece during the Greek–Italian War of 1940–1941. The author aims to examine the position of Macedonians within the Greek state and the impact of the armed conflict on their national and social circumstances. The study is based on historical sources and literature concerning Greek nationality policy toward the Macedonian population. The author points out that after the Treaty of Bucharest of 1913, a large part of the Macedonian lands became part of Greece, giving rise to a conflict between the Greek concept of the nation-state and the aspirations of the Macedonian population. During the interwar period, policies of colonization, Hellenization, and the suppression of manifestations of Macedonian national distinctiveness were pursued. Particular importance is attributed to the population exchanges following the Treaties of Neuilly and Lausanne, which brought about significant ethnic changes in the region. The article emphasizes that the government of Ioannis Metaxas intensified assimilationist policies through prohibitions on the use of the Macedonian language and increased repression against the “problematic” population. The outbreak of the Greek–Italian War found the Macedonians in a situation of strong national and political pressure. The conclusions indicate that the conflict of 1940–1941 was an important moment in the history of the Macedonian community, whose wartime experiences were closely linked to the preceding policy of assimilation pursued by the Greek state.